2010
DOI: 10.1039/c0py00039f
|View full text |Cite
|
Sign up to set email alerts
|

The development of poly(dendrimer)s for advanced processing

Abstract: A norbornenyl-based homopolymer that has a dendronised iridium(III) complex attached to every monomer unit has been synthesized. The dendronised iridium(III) complex is comprised of three facially arranged 2-phenylpyridyl ligands. Two of the ligands bear first generation biphenyl-based dendrons with 2-ethylhexyloxy surface groups attached and the third ligand is attached to the polymer backbone via a benzyloxy ester. The polymer was formed by ring opening metathesis using the Grubbs III catalyst and was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…A previous report has shown that at concentrations of up to 25 mg/mL, the viscosity of a dendrimer in solution only increased by 8% relative to that of the solvent. 36 The viscosity of poly(dendrimer) 3 at various concentrations in 1,2-dichlorobenzene at 20°C is shown in Figure 3. 1,2-Dichlorobenzene was determined to have a viscosity of 1.06 cSt and at a concentration of 25 mg/mL of poly(dendrimer) 3 in 1,2-dichlorobenzene the viscosity was 1.23 cSt.…”
Section: Resultsmentioning
confidence: 99%
“…A previous report has shown that at concentrations of up to 25 mg/mL, the viscosity of a dendrimer in solution only increased by 8% relative to that of the solvent. 36 The viscosity of poly(dendrimer) 3 at various concentrations in 1,2-dichlorobenzene at 20°C is shown in Figure 3. 1,2-Dichlorobenzene was determined to have a viscosity of 1.06 cSt and at a concentration of 25 mg/mL of poly(dendrimer) 3 in 1,2-dichlorobenzene the viscosity was 1.23 cSt.…”
Section: Resultsmentioning
confidence: 99%
“…Even larger porphyrin nanorings synthesised via a different method have been successfully characterised using dithranol matrix 32. The largest positive radical ions observed to date by MALDI‐TOFMS (using DCTB matrix) have been for a norbornenyl‐based homopolymer that has a dendronised iridium(III) complex attached to every monomer unit, which has an average molecular weight of 130 kDa 85. An example of a more fragile nanomaterial complex is the pentaphosphaferrocene copper(I) chloride nanospheroid,86 capable of encapsulating small molecules such as C 60 (Fig.…”
Section: Future Challengesmentioning
confidence: 99%
“…We have therefore focused on developing a new class of lightemitting material, namely poly(dendrimers) that have a nonconjugated backbone with dendrimer side-chains. [17][18][19][20] While polymers with small molecule iridium(III) complex sidechains [21][22][23][24][25] have been reported, the homopolymers have tended to have poor solubility 24,26 and the complexity of copolymers leads to more difficult syntheses and issues relating to reproducibility. In our first reports on phosphorescent poly(dendrimers) that were comprised of dendrimer side-chains the dendrimers were comprised of heteroleptic iridium(III) complex cores.…”
Section: Introductionmentioning
confidence: 99%